UHRF1, a Regulator of Methylation, as a Diagnostic and Prognostic Marker for Lung Cancer. (20th April 2020) - Goto, Daiki; Komeda, Kazuki; Uwatoko, Natsuki; Nakashima, Moeka; Koike, Mayu; Kawai, Kaho; Kodama, Yuta; Miyazawa, Ayako; Tanaka, Ichidai; Hase, Tetsunari; Morise, Masahiro; Hasegawa, Yoshinori; et al.
Abstract: We evaluated the value of UHRF1, a regulator of methylation, as a biomarker for lung cancer. UHRF1 is expressed at higher levels in both lung adenocarcinoma (AD) and squamous cell carcinoma (SQ); however, a meta-analysis showed that UHRF1 expression is correlated with worse survival in patients with AD but not in those with SQ. UHRF1 knockdown suppressed the growth of lung cancer cell lines through G1 cell cycle arrest in some cell lines. These results suggest that UHRF1 may server as a diagnostic marker for AD and SQ and as a prognostic marker for AD in lung cancer.